Community Forestry and the Sustainable Development Goals: A Two Way Street - Jong, W. de; Pokorny, B.; Katila, P.; Galloway, G.; Pacheco, P. (MDPI, 2018)
This paper analyses the contributions of community and smallholder forestry (CSF) to achieving the sustainable development goals (SDGs). A CSF-SDG positive feedback model is proposed; a model that holds that successful CSF positively contributes to 13 SDGs and 31 SDG targets. Recent CSF meta-studies have scrutinized factors leading to CSF success and found some 10 factors and conditions that contribute to that objective. If efforts towards reaching the SDGs support or enhance these factors leading to the greater success of CSF, this in turn would boost CSF contributions to the SDGs and their targets. As a result, CSF or active support for CSF, focusing on the 10 CSF factors that favor success, can be linked to 48 unique SDG targets. The analysis suggests that there is a significant opportunity to explore win-win options for efforts to support CSF and contribute to SDGs, but also for efforts to pursue the SDGs and targets that favor CSF, which will in turn boost the contribution of CSF to the SDGs. The case of CSF and its feedback links with the SDGs suggests that it may be relevant to identify interactions between the SDGs and other socio-ecological realities and related research.